Insights Into Forensic Features and Genetic Structures of Guangdong Maoming Han Based on 27 Y-STRs - Fan, Haoliang; Xie, Qiqian; Li, Yanning; Wang, Lingxiang; Wen, Shao-Qing; Qiu, Pingming (Frontiers in Genetics, 2021)
Maoming is located in the southwest region of Guangdong Province and is the cradle of Gaoliang culture, which is the representative branch of Lingnan cultures. Historical records showed the amalgamations between Gaoliang aborigines and distinct ethnic minorities had some influences on the sharping of Gaoliang culture, especially for the local Tai-kadai language-speaking Baiyue and Han Chinese from Central China. However, there is still no exact genetic evidence for the influences on the genetic pool of Maoming Han and the genetic relationships between Maoming Han and other Chinese populations are still unclear. Hence, in order to get a better understanding of the paternal genetic structures and characterize the forensic features of 27 Y-STRs in Han Chinese from Guangdong Maoming, we firstly applied the AmpFLSTR® Yfiler® Plus PCR Amplification Kit to genotype the haplotypes in 431 Han males residing in Maoming. A total of 263 different alleles were determined across all 27 Y-STRs with the corresponding allelic frequencies from 0.0004 to 0.7401, and the range of gene diversity (GD) was 0.4027 (DYS391) to 0.9596 (DYS385a/b). In the first batch of 27 Yfiler data in Maoming Han, 417 distinct haplotypes were discovered, and 9 off-ladder alleles were identified at 6 Y-STRs, in addition, no copy number variant or null allele were detected. The overall haplotype diversity (HD) and discrimination capacity (DC) of 27 Yfiler were 0.9997 and 0.9675, which demonstrated that the 6-dye and 27-plex system has sufficient system effectiveness for forensic applications in Maoming Han. What’s more, the phylogenetic analyses indicated that Maoming Han is one of Southern Han Chinese, and has a closely relationship with Meizhou Kejia, which uncovered that the role of the gene flows from surrounding Han populations in shaping the genetic pool of Maoming Han can’t be ignored. From the perspectives of genetics, linguistics, and geographies, the genetic structures of Han populations correspondence to the patterns of the geographical-scale spatial distributions and the relationships of language families. Nevertheless, no exact genetic evidence supports the intimate relationships between Maoming Han and Tai-Kadai language-speaking populations and Han populations of Central Plains in the present study.